A Discovery and Characteristics Description of Telosma puberula (Asclepiadoideae) in Mount Gedang Atas and Mount Ijo, Baturagung Mountain Yogyakarta - Widodo Widodo (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2014)
Population of Telosma puberula in community forest bushes was identified at S.07.48'.44.1